Perbedaan Rasio Trombosit Limfosit Kanker Serviks Tipe Karsinoma Sel Skuamosa Berdasarkan Diferensiasi - Muhammad Eko Fadhli Hendrinanto; Hariadi Yuseran; F.X. Hendriyono (Homeostasis, 2022)
Abstract: Cervical cancer is the second leading cause of death in women after breast cancer in Indonesia. Cervical cancer has several types of cells, the most common cell type is squamous cell carcinoma (75%), followed by adenocarcinoma (20%) and the rest are other types (5%). The degree of differentiation of cancer cells is the result of microscopic assessment of cancer cells based on the number of cancer cells undergoing mitosis, the similarity of the shape of the cancer cells to the original cells and the homogeneity of the cancer cells. The platelet to lymphocyte ratio (PLR) is related to the degree of cell differentiation. The progression of cervical cancer is influenced by the degree of cell differentiation. The higher of PLR, the worse degree of differentiation of the cancer cells and if the lower of the PLR, the better the degree of differentiation of the cancer cells. The results showed that 88 research subjects were recorded at the medical record installation of RSUD Ulin Banjarmasin and only 46 subjects (52%) met the inclusion criteria including 12 subjects (26%) well differentiated, 28 subjects (61%) moderately differentiated and 6 subjects (13%) ) is poorly differentiated. The mean for well-differentiated SCC obtained a value of 155.6 while the mean for poorly-differentiated SCC obtained a value of 269.9. The median for SCC with moderate differentiation was 208.4, the minimum value was 36.2 and the maximum value was 492.1. The ratio of platelets to lymphocytes between differentiations had no significant difference. Keywords: cervical cancer, degree of cell differentiation, PLR      Abstrak: Kanker serviks merupakan salah satu penyebab kematian kedua pada wanita setelah kanker payudara di Indonesia.Kanker serviks mempunyai beberapa tipe sel, tipe sel yang terbanyak adalah tipe karsinoma sel skuamosa (75%), diikuti oleh tipe sel adenokarsinoma (20%) dan sisanya merupakan tipe lain sebanyak (5%). Derajat diferensiasi sel kanker adalah hasil dari penilaian mikroskopis sel kanker berdasarkan jumlah sel kanker yang mengalami mitosis, kemiripan bentuk sel kanker dengan sel asal dan susunan homogenitas dari sel kanker. Rasio trombosit limfosit (RTL) berhubungan dengan derajat diferensiasi sel. Progresivitas kanker serviks dipengaruhi derajat diferensiasi sel. Semakin tinggi RTL maka semakin buruk juga derajat diferensiasi dan sebaliknya semakin rendah RTL maka semakin baik derajat diferensiasi. Hasil penelitian didapatkan 88 subjek penelitian yang terdata di Instalasi rekam medik RSUD Ulin Banjarmasin dan hanya 46 subjek (52%) memenuhi kriteria inklusi diantaranya 12 subjek (26%) berdiferensiasi baik, 28 subjek (61%) berdiferensiasi sedang dan 6 subjek (13%) berdiferensiasi buruk. Rerata untuk KSS diferensiasi baik didapatkan nilai 155,6 sedangkan rerata untuk KSS diferensiasi buruk didapatkan nilai 269,9. Median untuk KSS diferensiasi sedang didapatkan nilai 208,4, nilai minimum didapatkan 36,2 dan nilai maksimum didapatkan 492,1. Rasio trombosit limfosit antar diferensiasi memiliki perbedaan yang tidak bermakna. Kata-kata kunci: kanker serviks tipe KSS, derajat diferensiasi sel, RTL